2013
DOI: 10.1186/1757-7241-21-5
|View full text |Cite
|
Sign up to set email alerts
|

The Study Protocol for the LINC (LUCAS in Cardiac Arrest) Study: a study comparing conventional adult out-of-hospital cardiopulmonary resuscitation with a concept with mechanical chest compressions and simultaneous defibrillation

Abstract: BackgroundThe LUCAS™ device delivers mechanical chest compressions that have been shown in experimental studies to improve perfusion pressures to the brain and heart as well as augmenting cerebral blood flow and end tidal CO2, compared with results from standard manual cardiopulmonary resuscitation (CPR). Two randomised pilot studies in out-of-hospital cardiac arrest patients have not shown improved outcome when compared with manual CPR. There remains evidence from small case series that the device can be pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…[129][130][131][132][133] The most likely explanation is that inexperienced rescuers underestimate the time required to apply the device, 134 which leads to a significant decrease in CCF during the first 5 minutes of an arrest [135][136][137] despite increases in CCF later in the resuscitation. 138 There is evidence that pre-event "pit crew" team training can reduce the pause required to apply the device.…”
Section: Additional Logistic Considerationsmentioning
confidence: 99%
“…[129][130][131][132][133] The most likely explanation is that inexperienced rescuers underestimate the time required to apply the device, 134 which leads to a significant decrease in CCF during the first 5 minutes of an arrest [135][136][137] despite increases in CCF later in the resuscitation. 138 There is evidence that pre-event "pit crew" team training can reduce the pause required to apply the device.…”
Section: Additional Logistic Considerationsmentioning
confidence: 99%
“…The LINC (LUCAS in Cardiac Arrest) study was designed to evaluate the effectiveness and safety of an algorithm using mechanical chest compressions combined with defibrillation during ongoing compressions (mechanical CPR) compared with manual CPR according to guidelines. 16,17 The rationale for this design of the algorithm with mechanical chest compressions was based on studies suggesting the importance of compressions before defibrillation and a minimal hands-off interval. 4,18,19 The primary objective was to assess whether treatment with mechanical CPR would result in superior 4-hour survival in patients with out-of-hospital cardiac arrest compared with treatment with manual CPR.…”
Section: -4mentioning
confidence: 99%
“…Its protocol has been described in detail. 17 For inclusion, patients had to be adults with unexpected out-of-hospital cardiac arrest for whom an attempt of resuscitation was considered appropriate. Exclusion criteria were traumatic cardiac arrest (including hanging), age younger than 18 years, known pregnancy, and a body size too large or small to fit the chest compression device.…”
Section: Study Design and Algorithmsmentioning
confidence: 99%
“…63 There are manual versions of this device, as well as electrically and pneumatically operated versions. 64 One trial has shown improved survival to discharge when active decompression from a manual device was combined with the impedance threshold device, the latter enhancing the negative intrathoracic pressure generated during chest decompression.…”
Section: Active Compression and Decompression Cprmentioning
confidence: 99%